Drivers of leverage in Malaysia’s blue chip firm: the case of manufacturing sector / Arina Raihan Azlan - Azlan, Arina Raihan (Faculty of Business Management, 2017)
This aim of this study is to explore the drivers of leverage in Malaysian Blue Chip manufacturing firms and to investigate whether these drivers are supporting Pecking Order theory (POT) or Trade-off theory (TOT). Generally, POT suggest that there is no optimal capital structure as firms prefer to use internal funds as first choice, followed by debt and equity as a last resort to finance their business. TOT, on the other hand, suggest optimal capital structure can achieve by setting off the benefits of debt with cost. The investigation is performed using panel data procedures for a sample of 32 firms listed in Bursa Malaysia during 2010 until 2015. Variable used in this study is debt to equity ratior known as leverageas dependent variable, whereas asset tangibility, market to book value, degree of operating leverage, return on invested capital proxy for profitability, firm size and non-debt tax shield as independent variable. The variables areregressed with panel least square and tested with fixed effect (cross section).The results suggest that profitability and non-debt tax shield has a negative significant to debt to equity ratio. Market-to-book value, degree of operating leverage, and firmsize appear to have a positive significant to debt to equityratio. However, asset tangibility is negative related but does not appear significant to the leverage. It appeared that asset tangibility, profitability, market to book value and non-debt tax shield is consistent with Pecking order theory, while firm size and degree of operating leverage areaccording to trade-off theory.